Analysis of the Management and Utilization of Village Funds in Bantarjati Village, Klapanunggal District, Bogor Regency - Steffani Debora Auli; I Gusti Ketut Agung Ulupui; Tri Hesti Utaminingtyas (Journal of Business Innovation and Accounting Research, 2024)
This study aims to analyze the management and utilization of Village Funds in Bantarjati Village, Klapanunggal District, Bogor Regency. The research focuses on examining the village government's capacity to manage Village Funds in terms of financial reporting and fund disbursement during the 2022 fiscal year, despite various constraints encountered. These constraints include delays in budget disbursement, limited community participation, and the quality of human resources among village officials. This study employs a qualitative research design using a descriptive approach and a case study method. Primary data were collected through semi-structured interviews with five key informants from the village administration. Data analysis was conducted based on the regulatory framework stipulated in the Minister of Home Affairs Regulation (Permendagri) No. 20 of 2018 concerning Village Financial Management and the Bogor Regent Regulation No. 63 of 2022 concerning the Use of Village Funds. The data were analyzed using the Miles and Huberman qualitative analysis model. The findings indicate that Bantarjati Village has managed and utilized Village Funds appropriately and in compliance with prevailing regulations. The preparation, allocation, and reporting processes were implemented in accordance with statutory provisions, despite internal and external obstacles. Therefore, it can be concluded that although various challenges were encountered, Bantarjati Village was able to carry out the reporting cycle and fund distribution process in accordance with applicable regulations.